Combining High‐Throughput Synthesis and High‐Throughput Protein Crystallography for Accelerated Hit Identification. Issue 33 (9th July 2021) - Sutanto, Fandi; Shaabani, Shabnam; Oerlemans, Rick; Eris, Deniz; Patil, Pravin; Hadian, Mojgan; Wang, Meitian; Sharpe, May Elizabeth; Groves, Matthew R.; Dömling, Alexander
Abstract: Protein crystallography (PX) is widely used to drive advanced stages of drug optimization or to discover medicinal chemistry starting points by fragment soaking. However, recent progress in PX could allow for a more integrated role into early drug discovery. Here, we demonstrate for the first time the interplay of high throughput synthesis and high throughput PX. We describe a practical multicomponent reaction approach to acrylamides and ‐esters from diverse building blocks suitable for mmol scale synthesis on 96‐well format and on a high‐throughput nanoscale format in a highly automated fashion. High‐throughput PX of our libraries efficiently yielded potent covalent inhibitors of the main protease of the COVID‐19 causing agent, SARS‐CoV‐2. Our results demonstrate, that the marriage of in situ HT synthesis of (covalent) libraires and HT PX has the potential to accelerate hit finding and to provide meaningful strategies for medicinal chemistry projects. Abstract : Parallel, automated, and practical multicomponent reaction synthesis of high diversity acrylamides/ester libraries and HT protein crystallography (PX) yielded potent covalent inhibitors of the main protease of the COVID‐19 causing agent SARS‐CoV‐2. More general, integration of HT PX and HT synthesis into the "design‐make‐test‐analyze" cycle will open unprecedented horizons in medicinal chemistry.